Giovanni Giudici: from a diptych of unpublished papers. 'Notes for a Conference' and the first draft of 'The Last Time'. (Prassi Ecdotiche della Modernità Letteraria, 2021)
The essay presents two documents by Giovanni Giudici found in the section of the archive still kept by the heirs. We provide the transcription and the commentary of two papers that transmit an unpublished poetic reflection and of the typescript of the first draft of the poem "L'ultima volta".